Experimental Investigation of Steel Fiber Diameter, Volume Fraction, and Aspect Ratio on Concrete Mechanical Behavior - Arka Prava Das; Abul Hasan; Md. Ayanul Huq Chowdhury; Md. Iftakhar Ahmed (Journal of the Civil Engineering Forum, 2026)
Concrete is the most widely used construction material due to its versatility and ability to be molded into various shapes. However, it inherently exhibits little tensile strength, limited ductileness, and poor crack resistance, often leading to brittle failure. To address these limitations, modern construction increasingly incorporates fibers into concrete to enhance its mechanical properties, durability, and overall performance. Among various fiber types, steel fibers have demonstrated superior crack resistance and improved structural behavior. This study focuses on evaluating the flexural strength behavior of Steel Fiber Reinforced Concrete (SFRC) using M30 grade concrete. An experimental program was conducted involving the casting of 180 prisms (100 × 100 × 500 mm) and 360 cubes (100 × 100 × 100 mm) with steel fiber contents of 1%, 1.5%, and 2% and aspect ratios of 50, 60, and 70. The fiber used had a diameter of 1 mm. The experimental program was limited to evaluating the mechanical performance of the concrete using compressive strength, flexural strength, and splitting tensile strength tests. Special tamping. micromechanical analysis and different workability methods have been omitted. The results reveal that incorporating steel fibers significantly enhances the mechanical properties of concrete. Notably, a mix containing 1.5% steel fibers with an aspect ratio of 70 exhibited the highest strength improvements across all tests, including an 18% increase in compressive strength, a 35% increase in split tensile strength, and a 36% increase in flexural strength compared to control specimens. These findings demonstrate that optimized steel fiber reinforcement not only improves flexural behavior but also contributes to superior structural integrity, making SFRC a promising material for high-performance construction applications.